В горах Сихотэ-Алиня - Арсеньев Владимир Клавдиевич (1986)
Экземпляры: ЦБ; ф24; ф26 (20231130) / Инвентарный номер: 16602 / Цена: 2.50 / Сис.шифр: Р2 / Авт.знак: А 85 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6